Politik Seksual dalam Film Animasi Disney - Endah Triastuti (Antropologi Indonesia, 2006)
Using Roland Barthes's semiotics as a tool of analysis, this article intends to find out the implications made by Disney's changes on this story of Chinese women and people in general. Barthes's multilevel semiotics shows how the same medium-the animation Mulan-could be viewed from different perspectives. Disney claimed that Mulan is a message on women's heroism. This is based on Disney's convictions that Mulan is an animation produced with "respect to women and non-Western peoples." Through feminist frame of thought and knowledge of the differences between the original Chinese and the Disney version, women experienced multilayered subordinations in the animation. The first subordination against women occurs when a person is born as a girl. Based on myths, society gives a set of characterizations to women, called the feminine character. The character is used as the basis to subordinate women and repress them. The next subordination against women occurs when the feminine character, having been applied to women for as long as they live (and taken for granted), is applied to a certain thing, person or group. Thus, whatever is regarded as having the feminine characteristics are placed in a subordinate position, and thus experience repression. Using the ethnographic approach, the writer finds that the viewers of Mulan could be categorized into three groups based on their meaning of Mulan: the "lover" group, the "ironists" group, and the "hater" group. Key words: sexual politics, Disney, feminist postcolonial theory.